Probable enterotoxin-associated toxic shock syndrome caused by Staphylococcus epidermidis - William F. Pomputius; Samuel H. Kilgore; Patrick M. Schlievert (BMC, 2023)
Abstract Background We describe a case of a toxic shock-like syndrome in a child, which was associated with Staphylococcus epidermidis instead of Staphylococcus aureus or Streptococcus pyogenes, the usual causes of toxic shock syndrome. Case presentation The patient was an 8-year-old boy who developed a toxic shock syndrome-like illness, including fever, hypotension, and rash. The Staphylococcus epidermidis isolate was cultured from urine, but this organism was unavailable for toxin testing. Multiple blood cultures were negative. Instead, a highly novel assay was used on acute plasma from the patient which demonstrated the presence of the genes for superantigens, staphylococcal enterotoxins A, C, D, and E. Superantigens are the known causes of toxic shock syndrome. Conclusions Our study suggests strongly that Staphylococcus epidermidis was causing the TSS symptoms through the known Staphylococcus aureus superantigens. It is unknown how many other such patients exist; this should be explored. Of great importance is that PCR performed directly on blood plasma in the absence of microbial isolation could be used to demonstrate superantigen genes.